Contrastive focus is acquirable: An investigation of Russian contrastive focus with English/Russian bilinguals - Ionin, Tania; Luchkina, Tatiana; Goldshtein, Maria (Second language research, 2024)
This article reports on two experiments that examine the computation of contrastive focus in Russian on the part of adult English-dominant heritage speakers and second language learners of Russian, in comparison with baseline monolinguals. The first experiment uses an acceptability judgment task to determine whether bilingual and monolingual speakers use both contextual and prosodic cues to determine the location of contrastive focus. A follow-up experiment uses two prominence detection tasks in order to separately examine participants’ sensitivity to contextual vs. prosodic cues. The findings indicate that, at higher proficiency, bilingual speakers of Russian successfully use both contextual and prosodic cues to contrastive focus; with proficiency controlled for, heritage speakers do not have an advantage over second language learners in this domain. These findings are discussed in light of cross-linguistic influence and interface vulnerability.